2016
DOI: 10.1093/jnen/nlw054
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cathepsin B Alleviates Secondary Degeneration in Ipsilateral Thalamus After Focal Cerebral Infarction in Adult Rats

Abstract: Secondary degeneration in areas beyond ischemic foci can inhibit poststroke recovery. The cysteine protease Cathepsin B (CathB) regulates cell death and intracellular protein catabolism. To investigate the roles of CathB in the development of secondary degeneration in the ventroposterior nucleus (VPN) of the ipsilateral thalamus after focal cerebral infarction, infarct volumes, immunohistochemistry and immunofluorescence, and Western blotting analyses were conducted in a distal middle cerebral artery occlusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…A shRNA-induced knockdown of beclin1, a regulator of autophagy, reduces autophagy, astro/micro-gliosis, and neuronal cell death in the ipsilesional thalamus (100). In another study, cathepsin-B (CathB), a lysosomal marker that increases as a result of autophagosome degradation, has been shown to progressively increase in the thalamus through 28 days after stroke, and its expression corresponds with the increased astroglia/microglia activation and neuronal cell loss (101). Pharmacological inhibition of CathB reduces inflammation and prevents neuronal injury and apoptosis in the ipsilesional thalamus (101), indicating the importance of this gene and the autophagy process in secondary thalamic injury after stroke.…”
Section: Interrogation Studies In Secondary Thalamic Injury After Strokementioning
confidence: 99%
See 3 more Smart Citations
“…A shRNA-induced knockdown of beclin1, a regulator of autophagy, reduces autophagy, astro/micro-gliosis, and neuronal cell death in the ipsilesional thalamus (100). In another study, cathepsin-B (CathB), a lysosomal marker that increases as a result of autophagosome degradation, has been shown to progressively increase in the thalamus through 28 days after stroke, and its expression corresponds with the increased astroglia/microglia activation and neuronal cell loss (101). Pharmacological inhibition of CathB reduces inflammation and prevents neuronal injury and apoptosis in the ipsilesional thalamus (101), indicating the importance of this gene and the autophagy process in secondary thalamic injury after stroke.…”
Section: Interrogation Studies In Secondary Thalamic Injury After Strokementioning
confidence: 99%
“…Some studies have shown that interventions to prevent secondary thalamic injury may be beneficial for recovery of function after stroke. Below is a summary of studies that investigate the role of secondary thalamic injury through manipulating specific molecules involved in inflammatory responses, autophagy, Aβ deposition, and neuronal apoptosis (5,26,50,59,60,(99)(100)(101).…”
Section: Interrogation Studies In Secondary Thalamic Injury After Strokementioning
confidence: 99%
See 2 more Smart Citations
“…It is predicted that by 2030, the Chinese population aged ≥60 will be >300 million, and ~2/3 patients with primary cerebral vascular disease will be aged ≥60 years. In recent years, due to personal habits or environmental factors, the age of patients with primary cerebral vascular disease has gradually reduced ( 3 , 4 ). Cerebrovascular disease and CI are currently the leading cause of disability and the second leading cause of mortality in China ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%